“La estética de incertidumbre”: la (in)certeza de la realidad en la novela Dios puso una sonrisa sobre su rostro de Winston Morales Chavarro - Curzytek, Barbara (Studia Romanica Posnaniensia, 2018)
The article examines Winston Morales Chavarro’s novel Dios puso una sonrisa sobre su rostro. It reflects on one of its principal themes: the limitations in the perception of reality, and attempts to determine the boundaries between the fantastic and the neofantastic elements in the novel. The purpose of the article is to show that one of the main ingredients of the novel is the neofantastic.